Atopic dermatitis and chronic kidney disease: a bidirectional Mendelian randomization study - Zhang, Han; Yuan, Shuai; Li, Yong; Li, Doudou; Yu, Zengli; Hu, Lidan; Li, Xue; Wang, Yuming; Larsson, Susanna C. (Frontiers in Medicine, 2023)
Background: A bidirectional association between atopic dermatitis and chronic kidney disease (CKD) has been revealed in observational studies, whereas the causality of this association was unclear. We conducted a Mendelian randomization study to determine the bidirectional causal association between atopic dermatitis and CKD. Methods: Independent genetic instruments associated with atopic dermatitis and CKD at the genome-wide significance level were chosen from corresponding meta-analyses of genome-wide association studies. Summary-level data for atopic dermatitis were obtained from the EAGLE Eczema consortium (30,047 cases and 40,835 controls) and FinnGen consortium (7024 cases and 198,740 controls). Summary-level data for CKD were derived from CKDGen consortium (64,164 cases and 625,219 controls) and FinnGen consortium (3902 cases and 212,841 controls). The inverse-variance weighted method was used in the main analysis and supplemented with three sensitivity analyses. Results: Genetic predisposition to atopic dermatitis was associated with an increased risk of CKD. For a one-unit increase in the prevalence of atopic dermatitis, the odds ratio of CKD was 1.07 (95% confidence interval: 1.01-1.12). In the reverse Mendelian randomization analysis, the odds ratio of atopic dermatitis was 1.14 (95% confidence interval: 1.03-1.26) for a one-unit increase in the prevalence of CKD. The associations persisted in sensitivity analyses and no pleiotropy was detected. Conclusion: This Mendelian randomization study suggests a bidirectional positive association between atopic dermatitis and CKD.